The role of the NGAL biomarker in the assessment of early and prediction of late graft function in kidney transplantation from a living related donor - M. I. Kyrychenko (Zaporožskij Medicinskij Žurnal)
The aim. To study the role of NGAL in assessing the recovery of early graft function (GF) and in predicting GF in the first year after kidney transplantation (KT) from a living-related donor (LRD).